2021
DOI: 10.1371/journal.pone.0254234
|View full text |Cite
|
Sign up to set email alerts
|

Sperm-binding regions on bovine egg zona pellucida glycoprotein ZP4 studied in a solid supported form on plastic plate

Abstract: The zona pellucida (ZP) is a transparent envelope that surrounds the mammalian oocyte and mediates species-selective sperm–oocyte interactions. The bovine ZP consists of the glycoproteins ZP2, ZP3, and ZP4. Sperm-binding mechanisms of the bovine ZP are not yet fully elucidated. In a previous report, we established the expression system of bovine ZP glycoproteins using Sf9 insect cells and found that the ZP3/ZP4 heterocomplex inhibits the binding of sperm to the ZP in a competitive inhibition assay, while ZP2, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…Recently, we showed that bZP4 has a predominant binding activity for bovine sperm in a solid support assay [ 11 ]. The bZP4 polypeptide expressed in Sf9 cells included residues Lys-25 to Arg-464 and consisted of five regions: N-terminal ZP-N-like domain (Lys-25 to Pro-135, ZP-N1), trefoil domain (Asp-136 to Tyr-181), ZP-N domain (Gly-182 to Ala-289, ZP-N), hinge region (Ser-290 to Gln-311) and ZP-C domain (Pro-312 to Arg-464, ZP-C) ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we showed that bZP4 has a predominant binding activity for bovine sperm in a solid support assay [ 11 ]. The bZP4 polypeptide expressed in Sf9 cells included residues Lys-25 to Arg-464 and consisted of five regions: N-terminal ZP-N-like domain (Lys-25 to Pro-135, ZP-N1), trefoil domain (Asp-136 to Tyr-181), ZP-N domain (Gly-182 to Ala-289, ZP-N), hinge region (Ser-290 to Gln-311) and ZP-C domain (Pro-312 to Arg-464, ZP-C) ( Figure 1 A).…”
Section: Resultsmentioning
confidence: 99%
“…In pigs, ZP4 is responsible for the sperm-binding activity of the ZP3/ZP4 complex [ 10 ]. Recently, we showed that ZP4 binds to sperm in bovines [ 11 ]. The species difference in sperm-binding ZP glycoproteins suggests that sperm-ZP binding mechanisms are different amongst mammals.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations